Cardioprotective Effect of Quercetin in 5/6-Nephrectomized Rats: Focus on Myocardial fibrosis and Oxidative Stress - Tri Yuliani; Melva Louisa; Wawaimuli Arozal; Vivian Soetikno; Nafrialdi Nafrialdi; Indah D Dewijanti (Tropical Biopharmaca Research Center, IPB University, 2017)
Uremic cardiomyopathy is the leading cause of death in patients with chronic kidney disease. Fluid overload and oxidative stress play important roles in its pathogenesis. This study aims to determine the effect of quercetin on uremic cardiomyopathy in 5/6-nephrectomized rats. To our knowledge, its cardioprotective effect on uremic cardiomyopathy induced in rats by 5/6 nephrectomy has not been investigated yet. Uremia was induced surgically in male Sprague-Dawley rats via 5/6 nephrectomy. Quercetin was administered per orally at a dose of 100 mg/kg/day for 8 weeks prior to sacrifice. Meanwhile, captopril was administered at a dose of 10 mg/kg/day. Lipid peroxidation was assessed using TBARS reaction, while GPX activity was determined to explore the endogen antioxidant mechanism. Myocardial fibrosis was analyzed using Massons’ Trichrome staining and the level of NT-proBNP in plasma was measured as a marker of cardiac dysfunction. Nephrectomy 5/6 had no effects on plasma NT– proBNP levels, cardiac and plasma MDA levels, but induced mild myocardial fibrosis and significant increase in cardiac GPX activity in comparison with normal rat (p<0.05). However, administration of quercetin or captopril did not ameleriote those mild myocardial fibrosis and increased GPX activity. Uremic cardiomyopathy induced by 5/6 nephrectomy demonstrated mild myocardial fibrosis but preservation of cardiac function demonstrated by NT-proBNP levels. Increased of GPX activity in the nephrectomized-rats compared to the control rats (p<0.05) suggests induction of antioxidant defense mechanisms that might not be exhausted yet. This condition highlighted a compensatory phase which was unchanged following chronic administration of either quercetin or captopril.